Feasibility of ultra-high-resolution abdominal CT angiography in PCCT in outperforming conventional EICT - Ayx, Isabelle; Schwenke, Kay; Rotkopf, Lukas Thomas; Kayed, Hany; Büttner, Sylvia; Schönberg, Stefan; Thater, Greta (European journal of radiology, 2025)
Objective - Photon-Counting Computed Tomography (PCCT) offers significant advancements in aortic imaging, especially for vascular applications. Its Ultra-High-Resolution (UHR) mode enhances the visualization of small vascular structures, aiding surgical planning while reducing radiation exposure. This study assesses whether UHR abdominal aortic angiography with PCCT improves resolution and noise ratio compared to Energy-Integrating Computed Tomography (EICT) without increasing radiation dose. - Methods - In this retrospective study, 25 patients underwent Ultra-High-Resolution abdominal CT angiography (PCCT) and were compared to 25 patients, who underwent abdominal CT angiography on an EICT scanner. Ethical approval was obtained. Image quality was assessed using Signal-to-Noise Ratio (SNR), Contrast-to-Noise Ratio (CNR), and a five-point Likert scale. Radiation doses were compared using CTDIvol, DLP, and effective dose, with statistical significance set at p < 0.05. - Results - The PCCT group showed significantly lower radiation exposure (CTDIvol: 4.7 mGy vs. 7.3 mGy, p = 0.0081; effective dose: 3.4 mSv vs. 6.5 mSv, p = 0.0057). Although PCCT had higher SNR and CNR, differences were statistically significant only for renal arteries (p = 0.0432). Subjective image quality was significantly better for PCCT (p < 0.0001). - Conclusion - This study outlines the feasibility of UHR mode using PCCT in improving the contrast-to-noise and signal-to-noise ratio in patients undergoing abdominal CT angiography in the arterial phase as well as improved image quality of visceral arteries compared to EICT, accompanied by a significant reduction in radiation dose. This supports its recommending PCCT angiography for use in reducing patient exposure while improving image quality.
Gesehen am 08.10.2025